DETERMINATION OF THE ANTIMICROBIAL SUSCEPTIBILITY PATTERN OF ENTEROBACTERIACEAE IN A TERTIARY HEALTH CENTER OF NORTHEASTERN NIGERIA - Yahaya M; Sambo BZ; Anthony OO; Galadima BG; Mohammed MM; Baffa SI; Salma Muhammad G (Ntec Specialist, 2016)
Gram negative resistance particularly amongst species of Enterobacteriaceae has emerged as a worldwide threat affecting the efficacy of our commonly used antimicrobial agents. These threats affect the quality of care and results in prolonged hospitalization and increase in health care cost. We set out to evaluate the occurrence and profile of antimicrobial resistance from clinical isolates of Enterobacteriaceae in a tertiary health center of north-eastern, Nigeria. Method: Confirmed species of Enterobacteriaceae isolated from 225 patients that were admitted in various units of University of Maiduguri Teaching Hospital (UMTH) Maiduguri were tested for susceptibility to 6 antimicrobial agents; ampicillin (10µg), aztreonam (30µg), gentamicin (10µg), ceftriaxone (30µg), ciprofloxacin (5µg) and amoxicillin/clavulanic acid (20/10µg) using the clinical and laboratory standards institute (CLSI) breakpoints. Results: A total of 225 clinical variants of Enterobacteriaceae were isolated during the study period.The specie with the highest proportion was Klebsiella pneumoniae with 73(32.4%) and this was followed closely by Escherichia coli with 61(27.1%). The result of the susceptibility testing on this species of Enterobacteriaceae showed ampicillin (10µg) with the highest resistance of 118(52.4%) while aztreonam (30µg) has the lowest resistance of 58(25.8%). Conclusion: There is the existence of widespread resistance to mostly the beta lactam agents among species of Enterobacteriaceae with the exception of Aztreonam. Irrational use of antibiotics must be discouraged so as to reduce this emerging threat. Stringent infection control and antibiotic stewardship program should be established and sustained in our hospitals nationwide